Development of Branched ZnO Microrods: A Comprehensive Structural and Optical Characterization - ines dhifallah; faten rhouma; imen saafi; jamila bennaceur; wafa selmi; wissem dimessi; Radhouane Chtourou (Iranian Journal of Materials Science and Engineering)
In this study, a novel three-step method for the synthesis of ZnO and branched ZnO microrods was developed. Numerous techniques were used to analyze the obtained samples: photoluminescence (PL) spectroscopy, raman spectroscopy, fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive X-rays (EDX), ultraviolet-visible spectroscopy (UV-visible) and X-ray diffraction (XRD).  The XRD study and Rietveld refinement confirmed that the synthesized samples have the hexagonal wurtzite structure of ZnO without any impurity with the P63mc space group. To further verify our experimental results, structural parameters were calculated by First Principles Density Functional Theory (DFT) calculations and compared with experimental ones. A small decrease in the unit cell volume following the branching process was observed by the DFT calculations and Rietveld refinement results. Raman spectra showed peaks corresponding to the phonon modes of hexagonal wurtzite ZnO, which was consistent with the results of XRD and Rietveld refinement. SEM confirmed that ZnO and BZnO samples have hexagonal rod and branched rod shapes. BZnO showed stronger green PL emission but lower overall PL intensity compared to ZnO. The reduced photoluminescence (PL) intensity across all frequencies indicates enhanced separation of the photogenerated electron-hole pairs in branched ZnO (BZnO) due to decreased recombination.